Estimating the return on investment of the Bureau of Tobacco Free Florida tobacco control programme from 1999 to 2015. Issue 1 (22nd January 2021) - Nonnemaker, James; MacMonegle, Anna J; Mann, Nathan; Woodlea, Robyn; Duke, Jennifer; Porter, Lauren
Abstract : Objective: To assess the return on investment (ROI) of the Florida tobacco control programme, the Bureau of Tobacco Free Florida (BTFF), in terms of healthcare expenditure savings and mortality cost saved as a result of reduced mortality due to the programme from 1999 to 2015. Methods: We use a synthetic control method to estimate the impact of the BTFF on smoking-attributable mortality, years of life lost (YLL), healthcare expenditures, and the economic value of premature mortality due to smoking in Florida from 1999 through 2015. We calculated an ROI for healthcare expenditures and for the value of life years saved. Results: From 1999 to 2015, adult smoking prevalence in Florida averaged 0.98 percentage points lower than prevalence in the synthetic control states (19.6% vs 20.6%). The ROI over the period from 1999 to 2015 was 9.61 for healthcare expenditures and 112.44 for premature mortality. These ROIs suggest that for every US$1 of expenditure by BTFF, smoking-attributable healthcare expenditures decreased by almost US$11 and reductions in the economic costs associated with YLL due to smoking-attributable mortality totaled approximately US$113. Conclusions: Our results suggest the BTFF resulted in fewer YLL, substantial healthcare cost savings and substantial savings in terms of mortality costs. The positive ROIs for healthcare expenditures and premature mortality suggest that the BTFF is a good investment of public funds.